Plant-microbe community dynamics in rhizosphere: Reviewing the grassroots ecology towards sustainable agriculture - KHAN, DIBYENDU; KABIRAJ, ASHUTOSH; BISWAS, RAJU; ROY, RAJENDRA KR; BANDOPADHYAY, RAJIB (The Indian Journal of Agricultural Sciences, 2023)
The interaction between microbes and plants in rhizospheric environment is evident regarding sustainable development in agriculture. Microbes are involved in various metabolic activities in plant systems, which in turn help in plant health improvement. Eventually, plant-microbe interactions are connected with biogeochemical cycles. In this context, metagenomic study helps us to survey the microbial diversity in their natural niches, especially in rhizospheric regions. Noticeably, a diverse group of bacteria, fungi, and archaea are likely to be involved in plant growth promoting (PGP) activities. Variation in microbial communities in the rhizosphere depends on various parameters, such as soil organic matter, plant genotype, plant exudates, crop rotation, soil pH, nutrient cycling, etc. Some abiotic factors and chemical fertilizers have negative impact on crop productivity, influencing sustainable development of environment. Despite having negative impacts from climate change, microbes cope with this altered scenario and try to adjust themselves successfully and consequently promote plant growth by nutrient acquisition and stress tolerance approaches. Therefore, climate change has appeared as a big threat to the agricultural sector in recent past and this might be persistent in near future. However, the conservation of microbial diversity in the rhizospheric regions appears as one of the most promising options for long-term environmental sustainability.